Small-scale maize milling - International Labour Office; United Nations Industrial Development Organization (Geneva : The Office, 1984)
The book gives insight on the techniques machinery and expertise required for the milling of maize, especially in a small scale.
Bibliography: p. [135]-137.
gp. 22/01/2019
Loans
Keywords: Corn; Milling machinery